Pengaruh Investment Opportunity Set Dan Employee Stock Option Terhadap Retuen Saham - Yanti, Nur Hida; Akhmad Sigit Adiwibowo (Universitas Pamulang, 2024)
ABSTRACT This study aims to determine the effect of Investment Opportunity Set, Employee Stock Option on Stock Returns. Stock Return is measured using Capital Gain, Investment Opportunity Set is measured using Market Value to Book of Asset and Employee Stock Option is measured using ESOP Listed Share. The population in this study are all companies that implement ESOP listed on the Indonesia Stock Exchange that adopt ESOP for the period 2017-2021. The number of samples in this study were 13 companies obtained using Judgement Sampling. 65 data were obtained. The type of data in this study is secondary data with quantitative research methods. The analysis technique used is panel data regression analysis with a significance level of 5%. This research was processed using eviews 12 software and showed that (1) Investment Opportunity Set has an effect on stock returns (2) Employee Stock Option has no effect on Stock Returns. Keywords: Stock Return, Investment Opportunity Set, Employee Stock Option